Occurrence and risk indicators of increased probing depth in an adult Brazilian population - Susin, Cristiano; Valle, Patricia; Oppermann, Rui V.; Haugejorden, Ola; Albandar, Jasim M. (Journal of clinical periodontology, 2005)
Background/Aims: There is little information about the occurrence and risk indicators for periodontal diseases in Latin America. The present study describes the prevalence, extent and severity of periodontal probing depth (PPD) and assesses the association between demographic, behavioural and environmental risk indicators and the extent and severity of PPD in this population. Materials and Methods: The target population was urban adults aged 30 years in Rio Grande do Sul state in South Brazil. A representative sample was selected using a multi‐stage, probability, cluster sampling strategy and included 853 dentate subjects 30–103 years of age. A full‐mouth clinical examination was carried out at six sites per tooth on all permanent teeth, excluding third molars, and was conducted in a mobile examination centre. Results: Approximately 65% and 25% of the subjects and 19% and 5% teeth per subject had PPD 5 and 7 mm, respectively. 31.6%, 33.7% and 34.7% subjects had generalized, localized or no PPD 5 mm, respectively. Probing depth increased in prevalence with increasing age, and leveled off at around 50 years of age and beyond. PPD 5 mm was significantly higher in males than in females, and in non‐Whites than in Whites. Cigarette smokers had a significantly higher occurrence of PPD 5 mm than non‐smokers, and this relationship was dose dependent. A multivariate model showed that generalized PPD 5 mm was associated with subjects aged 40 years, males, non‐Whites and moderate or heavy cigarette smokers (relative risk ratios: 2.0, 2.0, 2.2, 2.4 and 6.8, respectively). Conclusion: Moderate and deep probing depth was a common finding in this urban adult Brazilian population. Older age, male gender, non‐White race and moderate and heavy cigarette smoking were significant risk indicators of increased PPD, and these may be useful indicators of periodontal disease high‐risk groups.